Constructing sports facilities using environment-friendly materials - Li, Rui; Zhai, Chenxi (Frontiers in Materials, 2025)
This study is focused on applying environment-friendly materials (EFM) to construct sports facilities for sustainability. The current status and future potential of using EFM in sports facility construction are concretely discussed with a thorough literature review and analysis. First, we discuss the concept and significance of EFM, especially in terms of its advantages in reducing carbon emissions and conserving resources: e.g., Europe carries out the EU Horizon 2020 plan, which invests 3.018 billion euros for studying climate action, environment, resource efficiency, and rare materials for green manufacturing. Second, the application of EFM in venue construction, e.g., sports stadiums, is comprehensively reviewed and evaluated, including using renewable materials, energy-saving technologies, and eco-friendly architectural designs. Third, the challenges and future developing trends of applying EFM in sports facility construction are discussed by considering constructional design and material selection. We find that EFM shows great potential in constructing sports facilities, playing a key role in promoting the sustainable development of sports facilities and a low-carbon economy.